Presumptive neural microsporidiosis in a young adult German Shepherd dog from rural Australia. Issue 8 (26th April 2021) - Birckhead, A; Combs, M; Croser, E; Montgomery, A; Peters, A; Stark, D; Malik, R
Abstract : Case report: A 1‐year‐old, neutered male German Shepherd was presented with a 5‐month history of episodic lethargy, intermittent fever, weight loss and a hunched posture. The dog was diagnosed with presumptive microsporidian meningoencephalitis based on cytological findings on cerebrospinal fluid analysis and a positive PCR test. The dog initially responded favourably to a 4‐week course of trimethoprim‐sulfadiazine, pyrimethamine and fenbendazole, and remained well for 12 weeks following cessation of treatment. Disease then recurred, and despite an initial positive response to treatment, he deteriorated and was euthanased 11 weeks later, 7.5 months after definitive diagnosis and 13 months after clinical signs were first reported. Conclusion: To the authors knowledge, this is the first case of canine microsporidiosis in Australia.